2019
DOI: 10.1038/s41598-019-55860-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and its receptor as therapeutic targets in glioblastoma multiforme

Abstract: Although prolactin (PRL) and its receptor (PRLR) have been detected in glioblastoma multiforme (GBM), their role in its pathogenesis remains unclear. Our aim was to explore their contribution in GBM pathogenesis. We detected PRL and PRLR in all GBM cell lines tested. PRLR activation or overexpression using plasmid transfection increased proliferation, viability, clonogenicity, chemoresistance and matrix metalloproteinase activity in GBM cells, while PRLR antagonist ∆1–9-G129R-hPRL reduced their proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 73 publications
(102 reference statements)
1
12
0
Order By: Relevance
“…Various studies have emphasized the role and impact of these pathways on the patients, survival, cancer development, and migration of cancer cells and the recurrence of GBM, thus affecting GBM patient survival rates [29,30] . Consistent with this study, the role of steroid hormones, prolactin (PRL) and its receptor (PRLR), and leptin-related signaling in GBM has been identi ed in some functional studies, making them potential therapeutic targets for future studies [31][32][33] . The role of oncoviruses in various cancers has also been identi ed.…”
Section: Discussionsupporting
confidence: 69%
“…Various studies have emphasized the role and impact of these pathways on the patients, survival, cancer development, and migration of cancer cells and the recurrence of GBM, thus affecting GBM patient survival rates [29,30] . Consistent with this study, the role of steroid hormones, prolactin (PRL) and its receptor (PRLR), and leptin-related signaling in GBM has been identi ed in some functional studies, making them potential therapeutic targets for future studies [31][32][33] . The role of oncoviruses in various cancers has also been identi ed.…”
Section: Discussionsupporting
confidence: 69%
“…A debated topic without a definitive answer today is the role of hormones [26][27][28][29][30]. Interestingly, we did note a small but significant difference related to age at diagnostic surgery, with female patients generally being older, which could suggest a role for hormonal factors.…”
Section: Discussionmentioning
confidence: 61%
“…While some studies have found a correlation of glioma incidence to exogenous hormone treatment, such as oral contraceptives or hormone replacement therapy, others have not [28,30]. Regarding the findings in GBM tumor tissue, a high expression of prolactin and the prolactin receptor has been shown to have a detrimental effect on survival in males only [29]. Interestingly, the androgen receptor (AR) gene has been found to be amplified in both male and female GBM, and AR RNA was overexpressed in more than 90% of the samples examined [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these overexpressed tumor suppressors, other interesting transcripts that are currently being considered as therapeutic targets of special interest against cancer and that were found downregulated after exposing HepG2 cells to Ch-SeNPs were ROR1 (FC = 0.50), PRLR (FC = 0.44), HMMR (FC = 0.40) and CENPI (FC = 0.29). While ROR1 knockdown resulted in decreased proliferation and migration but enhanced resistance to apoptosis and anoikis [ 48 ], PRLR overexpression has been linked with increased proliferation, viability, clonogenicity, chemoresistance and matrix metalloproteinase activity [ 49 ]. As for HMMR, its overexpression promotes germline stem cell self-renewal and intracranial tumor propagation [ 50 ], while upregulation of CENPI has been associated with tumorigenesis and drug resistance through chromosome instability [ 51 ].…”
Section: Resultsmentioning
confidence: 99%